Overrepresentation of the ACTN3 XX Genotype in Elite Canoe and Kayak Paddlers. Issue 4 (April 2015) - Orysiak, Joanna; Sitkowski, Dariusz; Zmijewski, Piotr; Malczewska-Lenczowska, Jadwiga; Cieszczyk, Pawel; Zembron-Lacny, Agnieszka; Pokrywka, Andrzej
Abstract : Abstract: Orysiak, J, Sitkowski, D, Zmijewski, P, Malczewska-Lenczowska, J, Cieszczyk, P, Zembron-Lacny, A, and Pokrywka, A. Overrepresentation of the ACTN3 XX Genotype in Elite Canoe and Kayak Paddlers. J Strength Cond Res 29(4): 1107–1112, 2015—The aim of the study was to examine the association between the ACTN3 R577X polymorphism in canoe sprint athletes (canoe and kayak paddlers) and their results at 200- or 1000-m distance. Eighty-six European white male athletes divided into 2 groups—successful, who were outstanding at national championships, and nonsuccessful in these competitions—and 354 nonathletic controls were included in this study. The R577X polymorphism of ACTN3 was typed using PCR-RFLP. ACTN3 genotype distribution among all tested athletes and controls was in Hardy-Weinberg equilibrium. The odds ratio (OR) for successful 1000-m athletes harboring the XX genotype compared with sedentary controls was 2.95 (95% confidence interval [CI]: 1.37–6.35), but the OR for nonsuccessful 200-m athletes having the XX genotype compared with controls was 2.64 (95% CI: 1.30–5.36). These results suggest that factors associated with the ACTN3 XX genotype in canoe and kayak paddlers might provide some competitive advantage in performance at 1000 m, but it seems to limit at 200 m. Further studies aimed at development of training strategies based on genetic factors are needed.